Incidence and prevalence of hypertension in 18–40‐year‐old patients referred for palpitations with normal cardiac monitor findings - Christopher Wasco; Zeryab Khan; Aimee Willett; Andrew Volio; Cody Carter; Aditya Kesari; Shaili Kothari; Andrew Scheidemantel; Katelyn Bennett; Jessalyn Schafer; Marie Lockhart; Nagesh Chopra (The Journal of Clinical Hypertension, 2024)
Abstract Sixteen percent of patients referred for cardiology evaluation are found to have no cause for palpitations. Studies show that hypertension intricately influences “heart rate” and “contractility,?” the key components of “palpitation.” While the prevalence of hypertension is 22.4% in 18–39‐year‐olds, the relationship between palpitations and hypertension remains unknown in this age group. In our study, we assessed the incidence and prevalence of hypertension over 5 years in 18–40‐year‐olds referred for palpitations who had no known arrhythmic cause for palpitations between January 1, 206 and December 31, 2017. We found that over a period of 2.2 (0.7–4.1) years, an additional 56% patients were diagnosed with stage 1 (65/130) and stage 2 (28/130) hypertension, increasing the prevalence from 16% at the start of the study period to 72% at the end of the study period (p < .0001). Hypertensive patients were obese (BMI: 29 [24–36] kg/m2 vs. 25 [22–31] kg/m2; p = .03), used nonsteroidal anti‐inflammatory drugs (NSAIDs) (62 vs. 35%; p = .04), had a stronger family history of hypertension (55 vs. 4%; p < .0001) and exhibited higher systolic (124[120–130] mmHg vs. 112[108–115] mmHg; p < .0001) and diastolic (80[76–83] mmHg vs. 72[69–75] mmHg; p < .0001) blood pressures. Hypertension is commonly diagnosed in 18–40‐year‐old predominantly white female patients referred for palpitations without a known arrhythmic cause. The possibility of untreated hypertension causing palpitations in this cohort needs further evaluation.